Neolithodes yaldwyni Ahyong & Dawson, 2006, sp. nov. ... - Ahyong, Shane T.; Dawson, Elliot W. (Zenodo, 2006)
Neolithodes yaldwyni sp. nov. (Figs. 1–4) Neolithodes brodiei.— Thatje & Lörz, 2005: 335 –336, fig. 2A [NIWA 3433, 3434 only; not N. brodiei Dawson & Yaldwyn, 1970]. Not Neolithodes brodiei.— Thatje & Lörz, 2005: 335 [NIWA 3432 = Paralomis birsteini Macpherson, 1988]. Not Neolithodes brodiei.— Thatje & Lörz, 2005: 335 [NIWA 3435 = Paralomis stevensi sp. nov]. Type material. HOLOTYPE: NIWA 3434, male (cl 141.5 mm, cw 124.1 mm, tcl 159 mm), N of Sturge I., Balleny Is., 67°13.22–11.97’S, 164°17.78–14.87’E, 522–538 m, TAN0402/226, RV Tangaroa, 3 Mar 2004. PARATYPES: NIWA 3433, 1 male (cl 120.0 mm, cw 108.7 mm, tcl 144.0 mm), seamount W of Sturge I., Balleny Is., 67°26.09–26.37’S, 163°52.98–51.79’E, 124–170 m, TAN0402/235, RV Tangaroa, 4 Mar 2004; NMNZ CR11002, 2 males (cl 101.7–103.6, cw 91.6–95.2, tcl 124.1–131.8 mm), between Scott and Balleny Is., 67°08–06’S, 170°54–47’E, 900–1160 m, RV San Aotea II, trip 2010, haul 180, E. Winslade, 14 Feb 2005; NMNZ CR11003, 1 male (cl 136.6, cw 131.1, tcl ... : Published as part of Ahyong, Shane T. & Dawson, Elliot W., 2006, Lithodidae from the Ross Sea, Antarctica, with descriptions of two new species (Crustacea: Decapoda: Anomura), pp. 45-68 in Zootaxa 1303 on pages 46-55, DOI: 10.5281/zenodo.173679 ...